2019
DOI: 10.5694/mja2.50061
|View full text |Cite
|
Sign up to set email alerts
|

Acute kidney injury in Indigenous Australians in the Kimberley: age distribution and associated diagnoses

Abstract: Objective To describe the frequencies of acute kidney injury (AKI) and of associated diagnoses in Indigenous people in a remote Western Australian region. Design Retrospective population‐based study of AKI events confirmed by changes in serum creatinine levels. Setting, participants Aboriginal and Torres Strait Islander residents of the Kimberley region of Western Australia, aged 15 years or more and without end‐stage kidney disease, for whom AKI between 1 June 2009 and 30 May 2016 was confirmed by an acute ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…In our present study, the serum lipid profile of repeatedly deep‐fried vegetable oil consumed rats showed significant hypercholesterolemia compared to raw oil‐fed rats. In acute kidney disease, the glomerular filtration rate is decreased, the concentration of serum creatinine and urea, end product of protein metabolism increases significantly (Higgins, 2016; Mohan, Atkinson, Rosman, & Griffiths, 2019). In the current study, both the concentration of creatinine and urea in the serum of FVO‐fed rats were significantly increased compared to the RVO group although raw oil feeding and exercise training groups have been found as benefitted to lower the creatinine and urea level in the blood (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In our present study, the serum lipid profile of repeatedly deep‐fried vegetable oil consumed rats showed significant hypercholesterolemia compared to raw oil‐fed rats. In acute kidney disease, the glomerular filtration rate is decreased, the concentration of serum creatinine and urea, end product of protein metabolism increases significantly (Higgins, 2016; Mohan, Atkinson, Rosman, & Griffiths, 2019). In the current study, both the concentration of creatinine and urea in the serum of FVO‐fed rats were significantly increased compared to the RVO group although raw oil feeding and exercise training groups have been found as benefitted to lower the creatinine and urea level in the blood (Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…In this issue of the MJA , Mohan and colleagues report the population burden and diagnoses associated with AKI in Indigenous people in the Kimberley . They identified cases of AKI (defined by Kidney Disease: Improving Global Outcomes [KDIGO] criteria: absolute increase in serum creatinine level in 48 hours of at least 26.5 μmol/L or an increase over 7 days of at least 50%) during 2009–2016 in primary care and hospital electronic record systems.…”
mentioning
confidence: 99%